Orthostatic hypotension is associated with decreased cerebrospinal fluid levels of chromogranin A in early stage of Parkinson disease - Kaiserova, Michaela; Prikrylova Vranova, Hana; Galuszka, Jan; Stejskal, David; Mensikova, Katerina; Zapletalova, Jana; Mares, Jan; Kanovsky, Petr (Clinical autonomic research, 2015)
An association between the CSF chromogranin A (CgA) and orthostatic blood pressure changes was investigated in 20 patients in the early stage of Parkinson disease (PD). There was a positive correlation between the CSF CgA and diastolic blood pressure change, when CSF CgA levels were lower in patients with orthostatic hypotension (OH). Decreased CSF CgA may be useful in predicting OH in the early stage of PD.
Keywords: Cerebrospinal fluid; ortostatická hypotenze; Humans; Tilt-Table Test; lidé středního věku; Female; test na nakloněné rovině; Hypotension, Orthostatic; chromogranin A; lidé; Biomarkers; Orthostatic hypotension; Parkinson’s disease; biologické markery; ženské pohlaví; Male; Middle Aged; Chromogranin A; mužské pohlaví; Parkinson Disease; Parkinsonova nemoc